Faktor - Faktor yang Berhubungan Dengan Rendahnya Kunjungan Lansia Ke Posyandu Lansia Di Desa Rambah Tengah Utara Wilayah Kerja Puskesmas Rambah Tahun 2015 - Romayani Daulay, Nana Aldriana, (Jurnal Martenity and Neonatal, 2016)
Elderly is old age stage in the development of individuals with an age limit of 60 years and older. Elderly posyandu is a health sevice for old people that focuses onÂ health promotion and preventive as well as curative and rehabilitative services. Types of health problems often experienced by the elderly is Toothache, diarrhea, asthma, Heat, Recurring Headaches, and the most widely experienced by the elderly is Cough and Colds 17.81% 11.75%. The purpose of this study is known Factors Associated With Low Visits of Elderly Posyandu In Rambah Tengah Utara Village Work Area of Rambah Primary Health Centre 2015. The research method is analytic survey with cross sectional design. Sampling technique is done by simple random sampling with a sample of 212 people. The data collection is done by using primary data questionnaire distributed to the elderly. The data analysis of this research is the analysis of univariate and bivariate analysis using Chi Square. Results of research on the degree of confidence (CI) 95% acquired Knowledge factor p value = 0.0001, p value = 0.014 education, distance and transportation p value = 0.0001, Family Support p value = 0.0001 and p value Kader Role = 0.0001. The conclusion of this study indicate that there is a significant relationship between knowledge, education, distance and transportation, Family Support, and Kader Roles with Low Visits of Elderly Posyandu In Rambah Tengah Utara Village Work Area of Rambah Primary Health Centre 2015. Suggestions for health workers / Kader IHC to improve counseling regarding health education for the elderly in order to gain understanding of the importance of health care is to utilize posyandu.